Reframing in dentistry: Revisited - Sivakumar Nuvvula; Rekalakshmi Kamatham; Ramasubbareddy Challa; Sharath Asokan (Wolters Kluwer Medknow Publications, 2013)
The successful practice of dentistry involves a good combination of technical skills and soft skills. Soft skills or communication skills are not taught extensively in dental schools and it can be challenging to learn and at times in treating dental patients. Guiding the child's behavior in the dental operatory is one of the preliminary steps to be taken by the pediatric dentist and one who can successfully modify the behavior can definitely pave the way for a life time comprehensive oral care. This article is an attempt to revisit a simple behavior guidance technique, reframing and explain the possible psychological perspectives behind it for better use in the clinical practice.